Menopause bootcamp : optimize your health, empower your self, and flourish as you age - Gilberg-Lenz, Suzanne; Korn, Marjorie (Harper Wave, an imprint of HarperCollinsPublishers, 2022)
Drawing on her twenty-year medical career, the doctor known for her "Menopause Bootcamp" gatherings helps readers not only survive the physiological and psychological transition, but embrace and even celebrate this remarkable developmental phase, which can be the start of something new and wonderful.